Changes in French purchases of pulses during an FAO awareness campaign - Badji, Ikpidi; Caillavet, France; Amiot, Marie Josephe (Frontiers in Nutrition, 2023)
Background: Pulses can play a key role in a well-balanced diet and are now recognized for their health and sustainability benefits. However, consumption remains quite low, motivating promotion efforts such as the “International Year of Pulses” declared by the Food and Agriculture Organization (FAO) in 2016. The present study aims to evaluate changes in the purchase of pulses before and after the FAO’s awareness campaign promoting the consumption of pulses in France and investigate potential differences across sub-populations. Methods: Purchase data come from Kantar Worldpanel 2014–2017. First, in order to understand demand for pulses, the influence of sociodemographic variables on the purchase of pulses in different forms (raw, processed, ultra-processed) is analyzed using a Box-Cox heteroskedastic double-hurdle model. Then, changes in purchasing before and after the FAO campaign were estimated using a two-way fixed effects model, controlling for price and sociodemographic variables. Results: On that period, the purchasing of pulses increased by 8.4% overall. The increase was greater for younger participants (+11.8%), people living in urban areas with over 200,000 inhabitants (+8.4%), and lower-income households (+7.1%). The 8.4% increase observed indicated that there was a gradual preferences change in favor of pulses and the impact of the awareness campaign was to boost expenditure on pulses by a further 2%. Conclusion: The FAO campaign coincided with an increase in the purchasing of pulses and may have had an enhancing effect. However, consumption still remains below the level advised by dietary guidelines. There is a need for more public information and communication on the health and sustainability benefits of pulses, the consumption of which can be promoted through supply and education interventions.